You are not logged in.
Thanks, I was having some mental issues at the time...
2(8x^3 + y^3)(8x^3 - y^3)Hmm .... the two similar terms can be further factored like this (2x+y)*(4x^2-2xy+y^2) ==> 8x^3 - 4x^2y + 2xy^2 + 4x^2y - 2xy^2 + y^3 ==> 8x^3 + y^3 (2x-y)*(4x^2+2xy+y^2) ==> 8x^3 + 4x^2y + 2xy^2 - 4x^2y - 2xy^2 - y^3 ==> 8x^3 - y^3 So:2(2x+y)*(4x^2-2xy+y^2)(2x-y)*(4x^2+2xy+y^2)
factor completely: 128x^6 - 2y^6I can expand it to: 2(8x^3 + y^3)(8x^3 - y^3)I know it can be expanded more but how would that go?
Powered by FluxBB